Escherichia coli small heat shock protein IbpA is an aggregation‐sensor that self‐regulates its own expression at posttranscriptional levels. Issue 1 (14th October 2020) - Miwa, Tsukumi; Chadani, Yuhei; Taguchi, Hideki
Abstract: Aggregation is an inherent characteristic of proteins. Risk management strategies to reduce aggregation are critical for cells to survive upon stresses that induce aggregation. Cells cope with protein aggregation by utilizing a variety of chaperones, as exemplified by heat‐shock proteins (Hsps). The heat stress‐induced expression of IbpA and IbpB, small Hsps in Escherichia coli, is regulated by the σ 32 heat‐shock transcriptional regulator and the temperature‐dependent translational regulation via mRNA heat fluctuation. We found that, even without heat stress, either the expression of aggregation‐prone proteins or the ibpA gene deletion profoundly increases the expression of IbpA. Combined with other evidence, we propose novel mechanisms for the regulation of the small Hsps expression. Oligomeric IbpA self‐represses the ibpA/ibpB translation, and mediates its own mRNA degradation, but the self‐repression is relieved by sequestration of IbpA into the protein aggregates. Thus, the function of IbpA as a chaperone to form co‐aggregates is harnessed as an aggregation sensor to tightly regulate the IbpA level. Since the excessive preemptive supply of IbpA in advance of stress is harmful, the prodigious and rapid expression of IbpA/IbpB on demand is necessary for IbpA to function as a first line of defense against acute protein aggregation. Abstract : Small heat shock proteins (sHsps), which are well‐conserved chaperones, are representative "sequestrases" that co‐aggregate with denatured proteins. We found that IbpA, an Escherichia coli sHsp, is a direct mediator for negative feedback regulation of sHsps via mechanisms including a self‐translation repression. Since IbpA in advance of stress is harmful, the rapid expression of sHsps on demand is necessary for IbpA to function as a first line of defense against acute protein aggregation.